Comparison of Removable Appliance and Aligner - Karlian Karlinda; Himawan Halim (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Teeth position shifting in the jaw arch has been achieved for a long time, using active removable orthodontic appliances. This technique has faced some technological advancement as seen with the creation of Invisalign transparent aligner systems, which features digitally conducted treatment plans. The outcome is, therefore, stored, analyzed, and modified through computer devices, using a 3-dimensional display. Meanwhile, the advantage of transparent aligners is seen in the ease of use, as manual adjustments are not needed during the treatment progression, as observed with the conventional removable appliances. At the initiation of treatment with digital 3-dimension, teeth movement is determined using a computer device, characterized by enhanced aesthetic physical appearance. This increases patients’ interest in the subsequent use of appliance to produce the desired results, within the specified time frame. This literature study is, therefore, aimed at creating an insight on technological developments in the use of active orthodontic treatment, alongside conventional removable appliances.